Fish Diversity and Conservation Perspectives of Gandak River, India - Srivastava, P. K. (Our Nature, 2013)
Study of 10 km stretch of Gandak River in Uttar Pradesh revealed the ichthyofaunal diversity, assemblage structure, distribution pattern, threat status, ornamental and commercially important fishes. In all 54 fish species were recorded of many commercially important fishes. Among these species 45% belong to lower risk near threatened (LRnt), 26% vulnerable (VU), 11% lower risk least concern (LRlc), 11% not evaluated (NE) and 7% endangered (EN) category. Cyprinidae 33% were most important followed by Bagridae (11%), Channidae (9%), Tetradontidae (5%). DOI: http://dx.doi.org/10.3126/on.v11i1.8246 Our Nature Vol.11(1) 2013: 76-84